Holistic Therapy to Improve Quality of Life in Chronic Disease Patients - Redemptus; Weraman, Pius; Umbu Roga, Andreas (Universitas Airlangga, 2023)
The concept of healthy-sick is no longer only related to the bio-psycho-social-spiritual aspects but also includes the physical and mental aspects. Chronic disease is a long-term and often incurable condition that requires continued management. Medical care, such as medication and surgery, is vital in managing chronic diseases. Non-medical treatments, such as positive thinking, a healthy diet, and fasting, can also significantly impact managing chronic diseases. Writing this article uses a library study or literature review. A holistic approach to health care can improve patient outcomes by improving physical and mental health, promoting better care coordination and communication, improving self-management skills, addressing psychosocial and spiritual needs, and providing patient-centric care.